FORMALIN: SEBUAH FENOMENA GUNUNG ES - Maman A. Djauhari (Jurnal Sosioteknologi, 2008)
Formalin is famous because of its danger. Although it has some advantages, it may give disadvantages for the layman. Figuratively, the 'formalin' phenomena are pervasive. For example, the stinky garbage that blocks the drainage. Another example is found in our low quality television programs. The high dose of 'formalin' is also found in many of our mass media, particularly in Playboy magazine. Furthermore, the formalin phenomenon, has affected both the Indonesia's noblesse artists and the intellectuals. It is proved by the fact that the former rely on the misleading belief"” the freedom of creation "“ in creating their art work; the later come up with misleading and low quality public policies that give drawbacks to the public. It is therefore necessary that Indonesian people be reminded of the hazard of those 'formalin' phenomena and be encouraged to participate in building a civilized nation which has not only a character but also intelligence; the nation which is not only educated but also uphold the existing norms.